Answer:
I attached the work to your problem below.
I hope it helps.
Answer:
B
Step-by-step explanation:
1. Given mathematical statement
![4x+3=x+5-2x](https://tex.z-dn.net/?f=4x%2B3%3Dx%2B5-2x)
So,
![\begin{array}{cc}4x+3=x+5-2x&\text{ Given}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7D4x%2B3%3Dx%2B5-2x%26%5Ctext%7B%20Given%7D%5Cend%7Barray%7D)
2. Rewrite it as
![4x+3=x-2x+5](https://tex.z-dn.net/?f=4x%2B3%3Dx-2x%2B5)
So,
![\begin{array}{cc}4x+3=x-2x+5&\text{ Commutative property of addition}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7D4x%2B3%3Dx-2x%2B5%26%5Ctext%7B%20Commutative%20property%20of%20addition%7D%5Cend%7Barray%7D)
3. Combine like terms
and ![-2x:](https://tex.z-dn.net/?f=-2x%3A)
![4x+3=-x+5](https://tex.z-dn.net/?f=4x%2B3%3D-x%2B5)
So,
![\begin{array}{cc}4x+3=-x+5&\text{ Combine like terms}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7D4x%2B3%3D-x%2B5%26%5Ctext%7B%20Combine%20like%20terms%7D%5Cend%7Barray%7D)
4. Add
to both sides:
![4x+3+x=-x+5+x\\ \\5x+3=5](https://tex.z-dn.net/?f=4x%2B3%2Bx%3D-x%2B5%2Bx%5C%5C%20%5C%5C5x%2B3%3D5)
So,
![\begin{array}{cc}5x+3=5&\text{ Addition property of equality}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7D5x%2B3%3D5%26%5Ctext%7B%20Addition%20property%20of%20equality%7D%5Cend%7Barray%7D)
5. Subtract 3 from both sides:
![5x+3-3=5-3\\ \\5x=2](https://tex.z-dn.net/?f=5x%2B3-3%3D5-3%5C%5C%20%5C%5C5x%3D2)
So,
![\begin{array}{cc}5x=2&\text{ Subtraction property of equality}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7D5x%3D2%26%5Ctext%7B%20Subtraction%20property%20of%20equality%7D%5Cend%7Barray%7D)
6. Divide both sides by 5:
![x=\dfrac{2}{5}](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B2%7D%7B5%7D)
So,
![\begin{array}{cc}x=\dfrac{2}{5}&\text{ Division property of equality}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bcc%7Dx%3D%5Cdfrac%7B2%7D%7B5%7D%26%5Ctext%7B%20Division%20property%20of%20equality%7D%5Cend%7Barray%7D)
Assignment: ![\bold{Simplify \ Equation: \ 7\left(3\sqrt{2}x\right)-3\left(3\sqrt{16}x\right)-3\left(3\sqrt{8}x\right)}](https://tex.z-dn.net/?f=%5Cbold%7BSimplify%20%5C%20Equation%3A%20%5C%207%5Cleft%283%5Csqrt%7B2%7Dx%5Cright%29-3%5Cleft%283%5Csqrt%7B16%7Dx%5Cright%29-3%5Cleft%283%5Csqrt%7B8%7Dx%5Cright%29%7D)
<><><><><><><>
Answer: ![\boxed{\bold{3\sqrt{2}x-36x}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cbold%7B3%5Csqrt%7B2%7Dx-36x%7D%7D)
<><><><><><><>
Explanation: ![\downarrow\downarrow\downarrow](https://tex.z-dn.net/?f=%5Cdownarrow%5Cdownarrow%5Cdownarrow)
<><><><><><><>
[ Step One ] Remove Parenthesis (a) = a
![\bold{7\cdot \:3\sqrt{2}x-3\cdot \:3\sqrt{16}x-3\cdot \:3\sqrt{8}x}](https://tex.z-dn.net/?f=%5Cbold%7B7%5Ccdot%20%5C%3A3%5Csqrt%7B2%7Dx-3%5Ccdot%20%5C%3A3%5Csqrt%7B16%7Dx-3%5Ccdot%20%5C%3A3%5Csqrt%7B8%7Dx%7D)
[ Step Two ] Simplify Equations
![\bold{7\cdot \:3\sqrt{2}x: \ 21\sqrt{2}x}](https://tex.z-dn.net/?f=%5Cbold%7B7%5Ccdot%20%5C%3A3%5Csqrt%7B2%7Dx%3A%20%5C%2021%5Csqrt%7B2%7Dx%7D)
![\bold{3\cdot \:3\sqrt{16}x: \ 36x}](https://tex.z-dn.net/?f=%5Cbold%7B3%5Ccdot%20%5C%3A3%5Csqrt%7B16%7Dx%3A%20%5C%2036x%7D)
![\bold{3\cdot \:3\sqrt{8}x: \ 18\sqrt{2}x}](https://tex.z-dn.net/?f=%5Cbold%7B3%5Ccdot%20%5C%3A3%5Csqrt%7B8%7Dx%3A%20%5C%2018%5Csqrt%7B2%7Dx%7D)
[ Step Three ] Rewrite Equation
![\bold{21\sqrt{2}x-36x-18\sqrt{2}x}](https://tex.z-dn.net/?f=%5Cbold%7B21%5Csqrt%7B2%7Dx-36x-18%5Csqrt%7B2%7Dx%7D)
[ Step Four ] Add Similar Elements
![\bold{21\sqrt{2}x-18\sqrt{2}x=3\sqrt{2}x}](https://tex.z-dn.net/?f=%5Cbold%7B21%5Csqrt%7B2%7Dx-18%5Csqrt%7B2%7Dx%3D3%5Csqrt%7B2%7Dx%7D)
[ Step Five ] Rewrite Equation
![\bold{3\sqrt{2}x-36x}](https://tex.z-dn.net/?f=%5Cbold%7B3%5Csqrt%7B2%7Dx-36x%7D)
<><><><><><><>
Answer: 0.004 (you can ask Siri this question and get the same answer)
a sample space, , which is the set of all possible outcomes.
A set of events , where each event is a set containing zero or more outcomes.
The assignment of probabilities to the events; that is, a function from events to probabilities.
pls make me brainlyest have a good day